Schamberg's disease: case report with therapeutic success by using colchicine - Maria Lopes Lamenha Lins Cavalcante; Paula Yoshiko Masuda; Fernanda Freitas de Brito; Ana Cecília Versiani Duarte Pinto; Gabriela Itimura; Adauto José Ferreira Nunes (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Pigmented purpuric dermatoses (PPD) include a spectrum of diseases with different clinical aspects, but with similar histopathological features. Specific clinical findings allow the division of PPD in variants. Schamberg's disease is the most common. Treatment is sometimes ineffective and recurrences are common. There are reports of patients who responded well to the use of colchicine. We report the case of a 32-year-old woman, previously healthy, with a history of onset of asymptomatic lesions in legs. She presented purpuric skin eruptions and brownish stains diffusely distributed in the lower limbs. Biopsy was compatible with PPD. We decided for the introduction of colchicine, with good clinical response. The patient has been followed on outpatient basis for ten months without recurrence.